The Addition of Adjuvant Chemotherapy to Radiation in Early-Stage High-Risk Endometrial Cancer: Survival Outcomes and Patterns of Care. Issue 5 (1st June 2017) - Boothe, Dustin; Williams, Ned; Odei, Bismarck; Poppe, Matthew M.; Werner, Theresa L.; Suneja, Gita; Gaffney, David K.
Abstract : Objective: Early-stage high-risk endometrial cancer (HREC) treated with adjuvant radiotherapy (aRT) alone has been associated with an increased risk of distant relapse. The addition of chemotherapy to radiotherapy (aCRT) may benefit overall survival (OS). We investigated the patterns-of-care and OS benefit of aCRT in HREC by analyzing a large national registry. Methods: Our query was limited to patients with the International Federation of Gynecology and Obstetrics stage IB and II HREC with either papillary serous, clear cell, or grade 3 adenocarcinoma, diagnosed between 2004 and 2012. Logistic and Cox regression analyses were utilized to identify predictors of aCRT use and OS, respectively. Survival analysis was performed with Kaplan Meier and log-rank methods. Propensity score matching was employed to decrease the potential influence of selection bias. Results: A total of 11, 746 patients were identified for analysis with 8206 (69.9%) receiving aCRT, and 3540 (30.1%) received aRT. Predictors of aCRT included International Federation of Gynecology and Obstetrics stage II (odds ratio [OR], 1.39; 95% confidence interval [CI], 1.22–1.57), papillary serous (OR, 9.44; 95% CI, 8.22–10.85) or clear cell (OR, 3.21; 95% CI, 2.59–3.97) histology, lymph nodes removed (OR, 1.48; 95% CI, 1.31–1.69), and receipt of brachytherapy alone (OR, 1.55; 95% CI, 1.36–1.78). Estimated 5-year OS was 75.2% for patients receiving aRT only and 79.2% for those receiving aCRT ( P < 0.001). When compared with aRT, aCRT was associated with improved OS on multivariate (hazard ratio, 0.78; 95% CI, 0.61–0.99) analysis. A univariate shared-frailty Cox regression after propensity score matching revealed persistence of the OS benefit with aCRT (hazard ratio, 0.74; 95% CI, 0.65–0.84). Conclusions: The addition of adjuvant chemotherapy to radiation in HREC is associated with improved OS. Multiple demographic and clinical factors significantly influence the choice of adjuvant therapy in this setting.